Silver Nanoparticles Recovery from X-ray Films using Humic and Fulvic Acids: Synthesis and Antimicrobial Applications - BANKOLE, Owolabi Mutolib; ALADEJANA, Temitope Michael; OMOSEBI, Julius Gbenga; ADESINA, Abiola Olanike; OLASENI, Segun Esan (ABUAD Journal of Engineering and Applied Sciences, 2025)
The current study investigates the recovery and synthesis of silver nanoparticles (AgNPs) from used x-ray photographic films as a sustainable and cost-effective strategy for scalable production. Silver was extracted using an alkaline NaOH solution and stabilised with humic (HA) and fulvic (FA) acids, demonstrating a green chemistry approach that enhances nanoparticle stability and biocompatibility. FTIR analysis confirmed the incorporation of functional groups for AgNP stabilisation, SEM revealed well-dispersed nanoparticles, and XRD verified their crystalline structure. The HA- and FA-stabilised AgNPs showed superior antimicrobial activity compared to pure AgNPs, with inhibition zones of 35 and 39 mm against Escherichia coli and Streptococcus pneumonia, respectively. The antibacterial effects of the synthesised particles were found to be concentration-dependent. This dual approach of waste photographic film valorisation and in situ nanoparticle stabilisation offers an eco-friendly pathway for functional AgNP production with potential applications in medical and environmental fields.